Pleistocene climatic cycling and diversification of the Andean treefrog, Hypsiboas andinus - Koscinski, Daria (2008)
Our understanding of the causes of diversification of Neotropical organisms lags behind that of Northern Hemisphere biota, especially for montane and temperate regions of southern South America. We investigated the mitochondrial DNA genealogical patterns in 262 individuals of the frog Hypsiboas andinus from 26 sites across the eastern ranges of the Andes Mountains in Argentina and Bolivia. Our phylogenetic analyses indicate at least three distinct lineages: one representing H. andinus from Northwestern Argentina and southern Bolivia, at least one H. andinus lineage from northern Bolivia, and one clade containing both H. andinus (from the southern portion of the species range) and its putative sister taxon Hypsiboas riojanus . Hypsiboas andinus samples from northern Bolivia are well differentiated and may represent distinct species. The northern Argentine H. andinus lineage and southern H. andinus /H. riojanus lineage likely diverged between 2 and 6 million years ago; their current sympatry may be the result of secondary contact due to range expansion after isolation during Andean uplift or may reflect cryptic species. Within the geographically extensive northern H. andinus clade, we found significant geographical structuring consistent with historical fragmentation and subsequent range expansion. The timing of this fragmentation and range expansion coincide with the Pleistocene, a time of extensive climatic cycling and vegetational shifts. Average divergence among clades is lower than those found for other Neotropical taxa, highlighting the potential importance of recent climatic history in diversification in the southern Andes.